Principles of Good Corporate Governance on LPD Performance in Klungkung Regency - Putu Kepramareni; Sagung Oka Pradnyawati; Ni Wayan Ratna Puspa Dewi (Global Academia Publisher, 2021)
This study explains and describes the influence relationship between Good Corporate Governance (GCG), which is corporate governance, and the performance of a financial institution in Bali Province, namely the Village Credit Institution (LPD). This study uses random sampling techniques in determining the sample where 162 respondents were obtained. The data source was obtained primarily through a questionnaire given to respondents from the LPD representing Klungkung Regency. The results showed that accountability in the principles of GCG had no effect on LPD performance in Klungkung Regency while transparency, responsibility, independence and fairness had a positive effect on LPD performance in Klungkung Regency.